(untitled) (diségno, 2022)
I do not know whether drawing is still a practice useful for design and architecture. Certainly, it is no longer an irreplaceable practice; freehand drawing, which used to mark the beginning of the design process, can be replaced by a computer visualization, by the construction of models in paper or wire or plasticine, by very effective photomontages, or even by lists of more or less emphasized words that begin to lead us into a maze of possible alternatives, of piazzas, of alleyways, of bypasses... [read more]